Asthikshaya in Geriatrics: An Ayurvedic Approach to Age-Related Bone Degeneration (International Journal of Food and Nutritional Sciences, 2022)
Asthikshaya(bone tissue depletion) is a significant concern in geriatrics, closely paralleling conditions like osteopenia and osteoporosis in modern medicine. As per Ayurveda, Asthikshaya results from the aggravation of Vata dosha, which plays a pivotal role in the deterioration of Asthi dhatu (bone tissue). The aging process naturally increases Vata, leading to bone degeneration, which manifests in the form of symptoms like bone pain, joint looseness, and fractures.This article explores the Ayurvedic perspective on Asthikshaya, examining the qualities and functions of Asthi dhatu and its relationship with other bodily tissues. Ayurveda emphasizes a holistic approach to managing bone health through dietary modifications, lifestyle adjustments, and therapeutic interventions, focusing on balancing Vata dosha to prevent further depletion of bone tissue. Key Ayurvedic treatments include snehana (oleation), Swedana (sudation), and Vasti (medicated enema), which are designed to nourish and strengthen Asthi Dhatu while addressing the imbalance of Vata. Additionally, therapies utilizing medicated oils and ghee processed with bitter-tasting herbs are highlighted for their role in supporting bone regeneration. Specific dietary recommendations emphasize the use of sweet, sour, and salty tastes, which help in pacifying Vata dosha. The article also underscores the importance of early intervention and proactive care in managing Asthikshaya, advocating for a preventative approach that begins in middle age to maintain bone health and quality of life in the elderly. Ayurvedic principles can be applied to slow down the progression of age related bone degeneration offering a natural and holistic alternative to conventional treatments for conditions like osteoporosis.